Study of Strategic Leadership Characteristics among Unofficial Time Nurse Supervisors in Nursing Service Departments, Srinagarin Hospital, Faculty of Medicine, Khon Kean University - Tantiyasawasdikul, Jitaree; Kaewkot, Sagheemas; Pawong, Taworn; Duangmun, Sasithorn; Pimta, Wanida; Paritawa, Janpen; Panjinda, Sununta; Krairiksh, Marisa (Srinagarind Medical Journal, 2023)
Background and Objective: Unofficial-time nurse supervisors were middle managers who use their knowledge and skills of management, decision making, creativity, and strategic vision building. As a result, they need to have the characteristics of strategic leadership. This study aimed to study the characteristic of strategic leadership of unofficial-time nurse supervisors working in Surgical and Orthopaedics and Eye/Ear/Nose/Throat/Larynx Nursing Departments, Srinagarind Hospital, Faculty of Medicine, Khon Kaen University. Methods: This was a corss-sectional descriptive study. Data were collected from 135 unofficial-time nurse supervisors in Surgical and Orthopaedics and Eye/Ear/Nose/Throat/Larynx Nursing Departments, Srinagarind Hospital, Faculty of Medicine, Khon Kaen University during August-September 2022 via an online questionnaire. Data were analyzed using descriptive statistics. Results: One-hundred and eighteen questionnaires were successfully completed and returned, then the response rate was 87.41%. The average age of unofficial-time nurse supervisors was 37.06 ± 8.81 years with 10-15 years of nursing experience (44.10%). Most were Baccalaureate degree prepared (89%). Approximately 48% of them worked as unofficial-time nurse supervisors in the Surgical and Orthopaedics department and 51.70% in the Eye/Ear/Nose/Throat/Larynx Nursing department and primarily more than 10 years of experience as unofficial-time nurse supervisors (59.00%). They all perceived high levels of overall strategic leadership (mean = 3.90 ± 0.55) and all subscales including human and emotional component (mean = 4.13 ± 0.56), high-level cognitive activity (mean = 3.96 ± 0.54), anticipating and creating a future (mean = 3.91 ± 0.60), revolutionary thinking (mean = 3.85 ± 0.62), gathering multiple inputs (mean = 3.80 ± 0.63), and creating vision (mean = 3.74 ± 0.64), respectively. Conclusions: Unofficial-time nurse supervisors of both departments had high levels of overall and each subscale of strategic leadership. The subscale of creating a vision had smallest mean value. Therefore, as nursing leaders of departmental level to enhance quality of nursing service, strategic leadership development for unofficial-time nurse supervisors focusing on creating vision would be beneficial.